Abstracts - Redaktionen, - (Politica, 1990)
Thomas M. Pallesen The Growth of Public Expenditure: Does Polilics matter? Jørgen Grønnegård Christensen Budgetreforms and Budgetbehavior. The Manipulation of Public Servants and Politicians and the Possibility to manipulate them Peter Munk Christiansen Public Expenditures in the 1980's: From Asymmetry to Asymmetrical Adjustment? Finn Kenneth Hansen The Distributional Consequences of Public Expenditures